2018
DOI: 10.1016/j.jcot.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Application of three dimensional printing in surgery for cam type of femoro-acetabular impingement

Abstract: Surgical treatment of femoroacetabular impingement (FAI) focuses on improving the clearance for hip motion and alleviation of femoral abutment against the acetabular rim. Cam type of impingement is managed by performing an osteochondroplasty to remove the excess impinging bone from the head neck junction, thus improving the head neck offset. This procedure can be done by safe surgical dislocation, arthroscopy assisted mini-open method or all arthroscopy technique. Whatever be the approach, adequate excision of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…In addition, this could be used for 3D printing based on MRI-based 3D-models. 3D Printing is a novel tool for preoperative planning of cam resection [ 54 , 55 ] and can influence the location of the planned osteoplasty [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this could be used for 3D printing based on MRI-based 3D-models. 3D Printing is a novel tool for preoperative planning of cam resection [ 54 , 55 ] and can influence the location of the planned osteoplasty [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…preoperative planning of cam resection [54,55] and can influence the location of the planned osteoplasty [56]. This study has the following limitations.…”
Section: Figmentioning
confidence: 98%
“…The BFS method was also used to measure the 3D head-neck ratio for quantitative analysis of cam deformity 14 and to fabricate the spherical gauge for interoperative evaluation. 30 In this study, the BFS method was used to mark the border of cam deformity on 3D-CT ( Figure 3) and displayed a larger cam size and distribution range (11:00-03:30) than all views with the AAM method, which indicated that the BFS method can be used on 3D-CT to display the entire cam deformity. As shown in Figure 3, it was noted that the inferior border of cam-r was not as far down as that on cam-bfs, so the radial view of the AAM method showed a smaller portion of the cam deformity.…”
Section: Discussionmentioning
confidence: 63%
“…21,23 While the AAM method is based on the concept of bestfit circle on 2D images, 19 the best-fit sphere (BFS) method has been used to fabricate a spherical gauge by 3D printing for locating cam deformity during open femoroplasty surgery. 30 Kang et al 11 proposed the BFS method in 2013 to quantify the location and size of cam deformity and indicated that it could be used on 3D-CT to define the cam border. Cam deformity would protrude outside such a BFS of the femoral head on 3D-CT and could then be defined.…”
mentioning
confidence: 99%
“…Cam-type femoro-acetabular impingement (FAI) can be treated by performing an osteochondroplasty to remove the excess impinging bone from the head neck junction of femur. Verma et al 12) reported a case of Cam-type FAI in an 18 year-old male, who underwent surgical treatment by osteochondroplasty. CT-based virtual surgical planning was conducted to design the femoral head and neck jigs, which were 3D printed and used intra-operatively to guide for adequate and optimum excision of bone at the femoral head neck junction.…”
Section: Femoro-acetabular Impingementmentioning
confidence: 99%